Building maintenance management competencies in high educational institution at Perak Tengah District / Abdul Muhaimin Husain and Wan Samsul Zamani Wan Hamdan - Husain, Abdul Muhaimin; Wan Hamdan, Wan Samsul Zamani (2019)
This overview discusses on the competency of building maintenance management for public high educational institution in Malaysia. Other than that, this review also looks on problems about the competency of building maintenance management. The study also found that the building maintenance organizations need to be careful when hiring people to work in the maintenance department at a building as there are some technical competencies that a person needs to know about building maintenance for him to practice in their routine work. A literature review is developed by using the secondary data collection method such as referring to journals, book, magazines, articles, newspaper and others.